Labor Market Regulation, International Trade and Footloose Capital - Tapio K. Palokangas (Institute of Labor Economics (IZA), 2017)
I examine the effects of globalization in countries where the employed workers support the unemployed and the governments control wages by regulating the workers' relative bargaining power. I use a general oligopolistic equilibrium model of two integrated countries with two inputs: labor and potentially footloose capital. National competition for jobs by labor market deregulation creates a distortion with suboptimal wages. The mobility of capital aggravates that distortion by increasing the wage elasticity of labor demand, which decreases wages and welfare even further. The delegation of labor market regulation to an international agent eliminates that distortion, increasing wages and aggregate welfare.
Keywords: C78; F16; F68; J52; 330; international trade; footloose capital; labor market regulation; capital market liberalization